Histological examination of the external oral apparatus of the tadpole of Dendropsophus microcephalus (Hylidae, Hylini) (2017)
I examined the oral morphology of tadpoles of D. microcephalus using histological sections in order to test several conflicting hypotheses. This study shows that there is a well-defined oral disc modified into a rigid tube and hidden beneath a fold of skin. There is one dermal ridge on the upper labium, but tooth rows and papillae are absent. I found that the oral morphology of D. microcephalus is similar to that of two other species of the D. microcephalus group.